eCM 2005
DOI: 10.22203/ecm.v010a04
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization of regenerated cellulose hydrogels induced by human bone marrow stromal cells

Abstract: The proliferation of cultured human bone marrow stromal cells (HBMSC) on regenerated cellulose hydrogels was assessed. Regenerated cellulose hydrogels showed good rates of HBMSC proliferation, the cells exhibiting a flattened morphology, and after 22 days in culture, the cells had homogeneously colonized the surface of the materials. Moreover, since the early days in culture, between the surface of the materials and attached cells a continuous granulated hydroxyapatite layer was formed. It has been previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…[141] More recently the same authors have shown that human bone marrow stromal cells not only proliferate on regenerated cellulose hydrogels but also deposit a layer of HAP. [142] These studies again show that phosphorylation is an efficient means to increase the nucleation and crystallization efficiency of a synthetic or semi-synthetic biomaterial.…”
Section: Carbohydratesmentioning
confidence: 86%
“…[141] More recently the same authors have shown that human bone marrow stromal cells not only proliferate on regenerated cellulose hydrogels but also deposit a layer of HAP. [142] These studies again show that phosphorylation is an efficient means to increase the nucleation and crystallization efficiency of a synthetic or semi-synthetic biomaterial.…”
Section: Carbohydratesmentioning
confidence: 86%
“…45 However, it is known that the cellulose crystallization process can be interrupted by addition of fluorescent brightening agents or cellulose derivatives to the media, which interact with nascent cellulose. [46][47][48][49] The structure of cellulose composites formed by the addition of different cellwall polysaccharides and reagents, like gluco-and galactomannans, xyloglucan, and pectin, were recently investigated using X-ray diffraction, 13 C CP/MAS NMR, and electron microscopy techniques. [50][51][52][53][54] Structural interactions between those polysaccharides have been studied, and some interesting properties of such composites were found, such as improved gel strength and stability, the alteration of both ribbon and microfibril structure, lower stiffness, and greater extensibility and strength.…”
Section: Microbial Cellulose As a Wound-healing Systemmentioning
confidence: 99%
“…18,19 In this study, it was envisaged to take advantage of cellulose due to its good match with the mechanical properties of cortical bone and its hydroexpansivity, therefore allowing a satisfactory primary fixation to hard tissue. 20 Materials surface properties influence the composition of the adsorbed protein compounds, which in turn regulates how cells respond to the material. [21][22][23][24] Understanding the relationship between material surface properties, adsorbed molecules, and cellular responses is essential to designing optimal material surfaces for implantation and tissue engineering.…”
Section: Introductionmentioning
confidence: 99%